DISEASES THAT ARE DIAGNOSED AND TREATED BY X-RAYS AND GAMMA RAYS - Sajad Kareem Khalaf Hassan; Sajad Riad Kiridi Hajm; Muntazir Kazim Eabd Alamir Hasuwn; Zahraa Jasim Mohammed (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
rays have long been one of the most effective tools in detecting and diagnosing diseases because of their effective and practical properties in diagnosing the various diseases that appear in the x-ray image. Diagnostic x- rays are considered an examination carried out using To see the internal anatomy of the body Accurately and pinpoint the tiny spots. The x-ray beam passes through the body, and is absorbed in different quantities, depending on the absorption capacity of the material. Dense materials such as bones and metal appear in white in the x-ray image, while air in the lungs appears in black, and muscles and fat appear in shades of grey. In some tests, we resort to introducing contrast dyes such as iodine or barium into the body to provide more details of the part to be imaged, such as imaging the bile ducts, spinal cord (myelography), urinary tract, and other parts that need the use of contrast dyes. in These methods enabled us to diagnose various diseases such as chest diseases and various cancers If a foreign body is detected or calcium calcifications are seen.